Corporate Social Responsibility PT. Bank Mandiri Case Study: Wirausaha Muda mandiri - Gautama, Taufan Daru; Bangun, Yuni Ros (Journal of Business and Management, 2012)
Indonesia is one of the biggest country in South East Asia. but unfortunately the entrepreneurial percentage in this country only 0.7% meanwhile to becoming a welfare country is must have 2% Ã‚Â or more entrepreneurial percentage. And also one of developing country in the world. In this final project, author wants to evaluate the program of Wirausaha Muda Mandiri, who was the Corporate Social Responsibility program from Bank Mandiri. Purposed to create new entrepreneur which will be the answer of the problem stated above.The Purpose of this final project is to achieve evaluations for community development program of PT. Bank Mandiri which is Wirausaha Muda Mandiri. This project purpose is to analyze the effectiveness of the program. The results of the program will also be analyzed to discover whether it is already accomplish its target or not. The Author will analyze the relation between every parties involved in implementing the program to determining the successes of entrepreneurial in the society and also participantTo achieved the objective above the Author using, some theory such as Theory Independent Literally, Community Development, Corporate Social Responsibility Theory, and Theory of CSR Programs effectiveness to society or environmental. And to get the result the Author using these methodology Research Design, Problem Identification, Data gathering, Data Analysis and Conclusion.And conclusion of this is research is Wirausaha Muda Mandiri has give big contribution by increasing entrepreneur rate in Indonesia, it shown that PT. Bank Mandiri already create 6300 new entrepreneur, who also give opportunity to create new job field, and decreasing unemployment rate in Indonesia. For the recommendation first is do some improvement in chain of command and controlling system, second PT. Bank Mandiri should make database of participantÃ¢â‚¬â„¢s business progress, as supporting device to easily maintain the participantÃ¢â‚¬â„¢s company, and the last is PT. Bank Mandiri should maintain all the participant, not only the winners but also Ã‚Â the non winning participant.Keywords: corporate social responsibility, wirausaha muda mandiri, case study.